Computational electronics : semiclassical and quantum device modeling and simulation /: semiclassical and quantum device modeling and simulation. ([2016?]) - Vasileska, Dragica; Goodnick, Stephen M (Stephen Marshall), 1955-; Klimeck, Gerhard
No abstract available